Analisis Simpang Tiga Bersinyal Pada Jl. Kebonsari - Jl. Satsui Tubun - Jl. Sudanco Supriadi, Kota Malang - Dhena, Elvianus Venansius; Arifianto, Andy Kristafi; Oktaviastuti, Blima (Fakultas Teknik Universitas Tribhuwana Tunggadewi, 2023)
This research focuses on the performance analysis of a signalized intersection located at the crossing of Jalan Sudanco Supriadi and Jalan Satsui Tubun in Malang City. Involving two or more intersecting roads, this intersection is the center of attention regarding its capacity changes, which can create challenges in terms of traffic, accidents, and congestion. The main objective of this study is to evaluate the performance of the intersection during the observation period and project the performance five years into the future. The research design in this study uses quantitative with descriptive research type. This research will analyze data related to traffic volume, capacity, saturation level, cycle delay time, green time, and vehicle queuing. The results concluded that the intersection has a road width of 11 m with two two-way lanes and a 1 m wide road shoulder. The vehicle volume reached 2628.45 skr/hour, while the capacity of the north, east, and south directions were 1,065.84 skr/hour, 997.79 skr/hour, and 886.61 skr/hour, respectively. The saturation level on the north approach is 1.059, east 0.721, and south 1.154. The delay value reaches 194.397 seconds/skr, with an adjusted cycle time of 77 seconds. The queuing opportunities on the north, east, and south approaches are 382 m, 58 m, and 371 m, respectively. This intersection is predicted to experience heavy traffic flow in the next five years, as a result of the estimated traffic volumes. This research provides an in-depth understanding of the traffic problems at the intersection and is expected to provide useful solutions for drivers who frequently cross the intersection of Jalan Sudanco Supriadi and Jalan Satsui Tubun in Malang City.